CapitaLand’s Strategy over the Years - Kozhanova, Maria (2011)
This work is based on facts and figures about CapitaLand, a company which is considered to be a leader in property market in Singapore and in the region. Within ten years of its existence it has expanded core businesses rapidly not only in the home country but also overseas, became the property company that works in retail, residential, commercial, hospitality and entertainment sectors, constructs and manages multipurposed complexes under Company’s brand. To survive during hard times Company set up its own financial division and thus invented new financial products in the Asian market. Company is famous in a property industry by its creativity, innovations and new incentives which find acknowledgement among clients, partners, rivals, peoples and governments. Company contributes a lot to societies where it works, makes enormous steps in protecting environment and philanthropy, follows an anti-corrupt policy showing an excellent example for others and receiving numerous prizes.The way to become one of the largest, one of the best, one of the most innovative companies wasn’t easy. How changes in a market situation reflected on Company’s strategy? What decisions were made and why? How Company’s strategy helped to overcome pressure from various institutions and at the same time remained profitable satisfying its stakeholders? What were the reasons of Company’s success? Can this company be named as entrepreneurial and sustainable? In this work I tried to analyse the information through Institutional Theories, find and give answers on all these questions. The work is written in a form of a case study and can become a helpful instrument for other students.